Backround of the Study Teachers’ Strategies for Implementing the Merdeka Curriculum in Elementery Schools in 3T Areas : A literature Review - bintan jahara; Mahpudin; Yuyun Dwi Haryanti; Mat Rahimi Yusof (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study is motivated by educational disparities in 3T areas (disadvantaged, frontier, and outermost regions), which are characterized by limited infrastructure, restricted access to technology, and insufficient teacher competence in implementing the Merdeka Curriculum. These conditions necessitate the development of adaptive, context-specific learning strategies. This study aims to analyze adaptive teaching strategies and examine the relationships among contextual challenges, pedagogical adaptation, instructional strategies, and their implications for teaching practices. The study employs a Systematic Literature Review (SLR) approach based on 15 relevant scholarly articles. The findings indicate that the dominant strategy is contextual learning (26.7%), followed by Project-Based Learning (20%) and differentiated instruction (13.3%). These results suggest that teachers develop flexible strategies by utilizing local contexts and adapting instructional methods accordingly. Furthermore, this study proposes a conceptual model that illustrates the dynamic relationships among contextual challenges, pedagogical adaptation, instructional strategies, and learning implications. The model highlights that adaptive teaching strategies serve as a mediating mechanism in implementing the Merdeka Curriculum in 3T areas, and underscores the importance of strengthening teachers' adaptive competencies.